Warning system improve the clinical outcomes in transfer patients with ST-segment elevation myocardial infarction. Issue 26 (2nd July 2021) - Fang, Hsiu-Yu; Lee, Wei-Chieh
Abstract : Abstract: A warning system included directly faxing electrocardiography information to the mobile phone immediately after an ST-segment elevation myocardial infarction (STEMI) diagnosis was made at a non-percutaneous coronary intervention (PCI) capable hospital. This study aimed to explore the outcomes after using a warning system in transfer STEMI patients. From October 2013 to December 2016, 667 patients experienced a STEMI event and received primary PCI at our institution. 274 patients who were divided into transfer group were transferred from non-PCI capable hospitals and connected to a first-line cardiovascular doctor by the warning system. Other 393 patients were divided into the non-transfer group. The transfer group still had a longer pain-to-reperfusion time and presented higher troponin-I level when compared with non-transfer group. There was no significant difference in the use of drug-eluting stent and procedural devices between non-transfer and transfer groups. The prevalence of different anti-platelet agents loading did not differ between non-transfer and transfer groups. Non-significant trend about higher prevalence of statin use was noted in transfer group (78.9% vs 86.1%, P  = .058). The transfer group presented similar clinical short-term results regarding both cardiovascular and all-cause mortality when comparing with non-transfer group. The transfer group provided non-significant trend about lower one-year cardiovascular mortality (10.7% vs 6.2%, P  = .052) and lower all-cause mortality (12.2% vs 6.9%, P  = .026) when compared with non-transfer group. There was a significant difference in the Kaplan–Meier curve of 1-year cardiovascular mortality between the transfer group and the non-transfer group ( P  = .049). After using the warning system, the inter-facility transfer group had comparable outcomes even though a longer pain-to-reperfusion time and a higher peak troponin-I level when comparing with non-transfer group.